The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1111/j.1476-5381.1987.tb16831.x
|View full text |Cite
|
Sign up to set email alerts
|

Nerve pathways involved in adrenergic regulation of electrical and mechanical activities in the chicken rectum

Abstract: 1 Peripheral nerve pathways responsible for adrenergic inhibition of mechanical and electrical activities in the chicken rectum and receptors mediating the adrenergic inhibition were investigated in isolated extrinsically-innervated rectum of the chicken. 2 Electrical stimulation ofthe anal end (Ra) or the ileal cut end (Ri) of Remak's nerve, or perivascular nerves (P) elicited relaxation of the rectum pretreated with atropine (0.5 JM) and hexamethonium (0.3 mM) to block the cholinergic and non-cholinergic, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The resting membrane potential ranged between -42 and -68 mV, giving a mean of -55-0±0-6 mV (n = 95). This value was somewhat larger than that of the longitudinal muscle of the chicken rectum (Komori & Ohashi, 1987). Some preparations (70%) were spontaneously active and exhibited spontaneous membrane depolarizations in the early period of each experiment, during which the resting membrane potential was -55 mV or more.…”
Section: Electrical Activitiesmentioning
confidence: 74%
See 2 more Smart Citations
“…The resting membrane potential ranged between -42 and -68 mV, giving a mean of -55-0±0-6 mV (n = 95). This value was somewhat larger than that of the longitudinal muscle of the chicken rectum (Komori & Ohashi, 1987). Some preparations (70%) were spontaneously active and exhibited spontaneous membrane depolarizations in the early period of each experiment, during which the resting membrane potential was -55 mV or more.…”
Section: Electrical Activitiesmentioning
confidence: 74%
“…The membrane depolarizations (referred to as slow action potentials in the Results), which are spontaneous or electrically evoked, in the circular muscle of chicken rectum are similar in temporal parameters and amplitude to the slow waves in other gastrointestinal smooth muscles of many species (see . The slow depolarization is unlikely to be electrotonic spread from the longitudinal muscle, because such slow changes in membrane potential have not been observed in the longitudinal muscle of chicken rectum (Komori et al 1980;Komori & Ohashi, 1987). The effectiveness of D600 in suppressing discharge of the slow depolarization can be interpreted as an indication for involvement of a Ca21 inward current in the generation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Ten birds were killed by an overdose of halothane anaesthetic. The rectum, jejunum and attached mesentery with Remak's nerve and blood vessels were quickly excised and immersed into cold modified Krebs'-Henseleit solution: 118.9 mM NaCl, 4.6 mM KCl, 1.8 mM CaCl 2 , 2.4 mM MgSO 4, 1.2 mM KH 2 PO 4 , 25.0 mM NaHCO 3 and 11.1 mM glucose bubbled with 5% CO 2 and 95% O 2 (Komori and Ohashi 1987) maintained at 4°C. The gut contents were flushed from the lumen and the tissue washed in several changes of fresh Krebs' solution.…”
Section: Tissuementioning
confidence: 99%
“…Electrophysiological and pharmacological studies have demonstrated that Remak's nerve participates in the regulation of gut motility (Bartlet and Hassan 1971;Hodgkiss 1984a,b;Komori et al 1986Komori et al , 1988Komori and Ohashi 1987). The nature of this control is unknown.…”
Section: Introductionmentioning
confidence: 99%